The feasibility of the health insurance projects in Iraq - Ali Abdulhussein Khaleel Alfadhel; Assistant Professor Dr. Ali Mahmood Ali Samaka; Dr. Sanaa Jasim Mohammed; Sadeq Tuma Rahi AL-murshedy (Global Scientific Publishing, 2023)
The aim of the research is to delve into the contents of health insurance and determine its importance, foundations and positive impact on the health sector. It provides a financial vision and integrated feasibility for health insurance companies and health service companies, by calculating the break-even point and expected profits of companies. It has used the descriptive approach (a questionnaire form) and the quantitative approach through (financial indicators based on official statistics).
Keywords: approach; quantitative; expected; feasibility